The future of orientalist trends on internet sites and their impact on Qur’anic studies - Yousef A. Baker, El-Ebiary; Reda Owis, Hassan Serour; Mukhamad Hadi, Musolin Subagio (2020)
Orientalist trends on Internet sites differ from the old classic form of Orientalism, and these sites have varied among sites for Middle Eastern studies and sciences or politically or socially specialized research centers and so on. There is no doubt that the Orientalist movements have provided some services for Quranic studies in the indexing, translation, and investigation of manuscripts ... etc. but they have been right in matters and wrong in others, as some Orientalists attacked the Qur’an and its sciences, which had a significant negative impact among the generation of Muslims. The orientalist’s view of the Holy Qur’an varied in terms of holiness, belief and idea in each of them, so their perception of the Qur'an differed accordingly. There are literatures that require consideration, attention, and even republishing for the goodness that it contains, and there are works that needed to review supported by arguments and statement and making the people aware of it and even should use our all sources to stop it from republishing it again. Likewise, among the Muslims who adopted the technique of the orientalists and their literature as a model for himself and started repeating and spreading some of their suspicions (uncertainty regarding to Islamic studies) either intentionally or being ignorant of what he means, so he should be corrected if he is unaware of it or she should be answered by arguments if he was intended to do so.